Análise e projeto de um conversor NPC para interligação de sistemas de conversão de energia à rede elétrica - Santos, Cícero Alisson dos (2011)
This work deals with the study of a three-level inverter with Neutral Point Clamped (NPC), proposed for the interconnection of energy conversion systems to the grid. In order to accomplish a complete study an inductive L is proposed and, vector control techniques, and PLL technology as synchronization method are used. Equations are developed for the determination of the losses of the converter, which can be applied to various PWM techniques. Three Modulation techniques are presented: Phase Disposition modulation (PD), modulation with injection of the third harmonic (THIPWM) and carrier-based space vector modulation (SVPWM-CB). The complete modeling system is presented, as well as an example for designing a system of 6 kW. Numerical simulations are performed for different study cases, validating the converter design and modeling developed. The simulation results show that the proposed NPC converter is fully satisfactory, the converter being able to control the power flow (unity power factor) and deliver to the reactive network when required.